Manichaica Taurinensia - Lieu, Samuel N. C. 1950-; Morano, Enrico 1951-; Pedersen, Nils Arne 1959-; International Association of Manichaean Studies; Università degli studi di Torino; Museo d'arte orientale (Turnhout Brepols, 2022)
The volume contains the proceedings of the ninth international symposium of the International Association of Manichaean Studies (IAMS) held at the University of Turin (11th-15th September, 2017) and covering all major aspects of Manichaean studies. This new volume brings the research on many aspects of Manichaeism up to date and offers also first editions or re-editions with new interpretations of Manichaean texts in the languages used by the Eastern and Western Manichaeans. It includes important studies on Manichaean Art, and on newly discovered Manichaean texts in Chinese and Parthian from Xiapu in South China
Keywords: Konferenzschrift